Eye Position Shifts Body Sway Under Foot Dominance Bias in the Absence of Visual Feedback - Tamaru, Yoshiki; Matsugi, Akiyoshi (Frontiers in Neurology, 2022)
[Purpose] The purpose of this study was to investigate whether information on extraocular muscle proprioception without visual information affects postural control. [Methods] Thirty-five healthy young volunteers participated in the study. Postural control outcomes included the center of pressure (CoP) for static standing, the total length of the sway of the CoP (LNG), and the sway area (SA), as well as the mean CoP in the mediolateral and anteroposterior directions. The following five eye-fixing positions were used: eye-up (E-Up), eye-down (E-Down), eye-right (E-Right), eye-left (E-Left), and eye-center (Center eye position). One-way ANOVA and Bonferroni correction was performed for statistical processing. Electrooculograms were recorded to detect eye orientation errors, measured with the eyes closed. [Results] The results of this study showed no significant difference between the LNG and SA results when comparing respective eye positions (E-up, E-down, E-right, E-left) relative to E-Center (control). However, the average CoP was shifted to the right at E-Up, E-Down, and E-Left. [Conclusion] These findings indicate that postural control may be affected by eye-body coordination depending on the position of the eyes, even without visual information.